Biocomputing 2006 2005
DOI: 10.1142/9789812701626_0043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Peroxisome Proliferators-Activated Receptor (Ppar) Gamma 3 Gene on Bmi in 1,210 School Students From Morelos, Mexico

Abstract: Little research has been undertaken on risk factors for obesity in young people in Latin America, including Mexico, despite the fact that obesity constitutes the number one public health problem in Mexico. Our objective was to investigate the effect of the Peroxisome proliferators-activated receptor (PPAR)_3 gene on BMI measured among adolescents collected from a cohort study originally designed for epidemiological studies. METHODS: Blood samples and anthropometric measurements were collected from 1,210 out of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 7 publications
1
4
0
Order By: Relevance
“…The lower concentrations of adiponectin found in boys with the Ala allele were also seen in young adult males from a Japanese cohort (22), suggesting interaction with the adiponectin gene. The screening analysis using BMI did not reveal any significant association with the Ala allele, which is consistent with recent results from an 11 to 24-year-old cohort from Mexico (1210 students) (12). In summary, we found evidence of a possible effect of the Ala allele at the Pro12Ala locus in the PPARg gene on adiposity indices in boys, and SFA intake and insulin indices in girls.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The lower concentrations of adiponectin found in boys with the Ala allele were also seen in young adult males from a Japanese cohort (22), suggesting interaction with the adiponectin gene. The screening analysis using BMI did not reveal any significant association with the Ala allele, which is consistent with recent results from an 11 to 24-year-old cohort from Mexico (1210 students) (12). In summary, we found evidence of a possible effect of the Ala allele at the Pro12Ala locus in the PPARg gene on adiposity indices in boys, and SFA intake and insulin indices in girls.…”
Section: Discussionsupporting
confidence: 91%
“…This has been attempted by several groups, with largely inconsistent findings (10)(11)(12)(13). It has recently been shown that in young children (13), the Pro12Ala polymorphism is associated with increased adiposity exclusively in girls.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous genes related to fatty acid transport and metabolism require regulation of the PPARγ gene at the transcriptional level. PPARγ gene polymorphisms are reportedly relevant to the components of MS; however, other studies have shown different results (Hu et al, 2004;Chen et al, 2006;Jaziri et al, 2006;Gaulton et al, 2008;Cho et al, 2009;Gallicchio et al, 2009;Matsuo et al, 2009;Bego et al, 2011). Understanding the relationship of the high incidence of MS and PPARγ gene polymorphisms is important for determining the mechanism of MS occurrence and development as well as for identifying molecular markers that could be used for early diagnosis and prognosis.…”
Section: Discussionmentioning
confidence: 99%
“…This value is close to the allele frequency of rs3856806T in the Australian population (16.3%; Evans et al, 2001), is higher than that in the South American (13%; Haseeb et al, 2009), Indian (12.3%;Costa et al, 2009), and Italian and French populations (13.3%; Hasstedt et al, 2001), but lower than that among the Han population (21.2%; Liu et al, 2008). Studies examining the relationship between the rs3856806 polymorphism and MS suggest that individuals carrying the T allele show clearly reduced rates of lipid metabolism disorders and high blood pressure, obesity, and diabetes (Chen et al, 2006;Jaziri et al, 2006;Gaulton et al, 2008;Cho et al, 2009;Gallicchio et al, 2009;Bego et al, 2011). We found that the individual risk of MS in the Kazakhs carrying the T allele was 0.694 times higher than that in Kazakhs carrying the C allele.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation